A Call for Emotional Intelligence Skills Training Curricula at Christian Colleges. Issue 2 (4th May 2018) - Dustman, Teresa
Abstract: Although emotional intelligence is an increasingly popular research topic regarding academic success, only one study regarding the topic has been conducted among Christian higher education student bodies. The Bible does not mention the term emotional intelligence; however, there are many biblical accounts of negative behaviors as a result of people succumbing to their emotions. Skills training, in the context of Christian colleges, would teach students how to commit emotional health to the will of God, how to process emotions and would provide life skills that will assist with the decision-making process.